Temporal evolution of the environmental footprints of intensive farming across England - Yusheng Zhang; Adrian L. Collins (PLoS ONE, 2026)
The agriculture sector continues to face expectations regarding documenting its unintended environmental footprints through time given increasing awareness of the need to deliver food more sustainably. Accordingly, the work reported in this paper used a process-based modelling framework evaluated previously to examine the temporal evolution (2010, 2016, 2021) of the environmental footprints of intensive farming systems across England. The results were computed at Water Management Catchment scale given the use of this spatial unit for policy reporting purposes. Environmental footprints focused on Global Warming Potentials over 20- (GWP20) and 100-year (GWP100) horizons, eutrophication potential (EP) and acidification potential (AP). Both GWP20 and GWP100 were included to characterise the short- and long- term impacts. Important structural changes in agriculture included a 3.7% increase in the area of land under ‘general cropping’ and a 2% reduction in that under dairy. There was a corresponding reduction of the registered cattle populations by 4% in 2016 and 12% in 2021, relative to 2010. At the same time, the number of sheep and lambs increased by 9% in 2016 and 4% in 2021. These farm structure changes in 2021 were computed to result in respective median reductions in GWP100, EP and AP of 18%, 13% and 21% compared with 2010. Eutrophication potential exhibited lower overall reductions wherein 28 water management catchments exhibited <5% reductions, with a maximum reduction of ~45%. In comparison, corresponding maximum reductions in GWP20, GWP100 and AP were modelled at 76%, 64% and 54%, respectively, with 17, 15 and 7 water management catchments exhibiting <5% reductions. Modelling suggests a downward change in environmental footprints but there are challenges in directly linking predicted temporal trends with existing and available monitored data.